The Aesthetic of Desire and the Feminine Path of Individuation: The Case of Forough Farrokhzad. Issue 2 (1st December 2021) - Vali-Zadeh, Mahdieh
Abstract: Much has been said about the influential role of Forough Farrokhzad (1934–1967) in developing a feminine language in modern Iranian love poetry. Despite this, scholars have not systematically or theoretically examined what I call 'the poetics of individuation' in Forough's lyrics. The present article analyses Forough's poetic and individual paths of development as two inevitably parallel and intertwined routes. The article theorises that by removing a pre-imposed patriarchal sense of sin with regard to feminine love, Forough deconstructed the masculine narrative of good poetry in five highly significant ways via the feminine and self gaze. The article concludes that the poet's commitment to poetry as a platform of expression was a means of her liberation and individuation as an independent feminine poet with voice and agency.